2020
DOI: 10.1021/acsami.0c13045
|View full text |Cite
|
Sign up to set email alerts
|

Pseudocapacitive Ti-Doped Niobium Pentoxide Nanoflake Structure Design for a Fast Kinetics Anode toward a High-Performance Mg-Ion-Based Dual-Ion Battery

Abstract: Magnesium-ion batteries (MIBs) have received increasing attention for next-generation energy storage recently because of the natural abundance, high capacity, and dendrite-free deposition of Mg. However, their applications are hindered by irreversible Mg anode plating in conventional electrolytes and the lack of cathode materials, demonstrating high working voltage, satisfactory Mg 2+ diffusivity, and long cycling life. In this work, we first developed a novel magnesium-ion based dual-ion battery (Mg-DIB) by u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 68 publications
4
45
0
Order By: Relevance
“…Recently, Yang et al . reported on a Mg‐based DIB cell using expanded graphite as cathode and Ti‐doped niobium pentoxide nanoflakes as fast kinetics anode [7i] …”
Section: Introductionmentioning
confidence: 99%
“…Recently, Yang et al . reported on a Mg‐based DIB cell using expanded graphite as cathode and Ti‐doped niobium pentoxide nanoflakes as fast kinetics anode [7i] …”
Section: Introductionmentioning
confidence: 99%
“…By calculating the b values of the three REDOX peaks, it is found that the three b values are all between 0.5 and 1, which means that the discharge capacity is jointly contributed by capacitor and electrochemical reaction during the charging and discharging process [31]. The b values corresponding to Peak1, Peak2 and Peak3 are 0.62, 0.53 and 0.51, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies on the charge storage mechanism in batteries have found that there is an electrochemical behavior of pseudocapacitance during charge and discharge. Pseudocapacitance refers to a supercapacitor in which highly reversible chemical absorption and REDOX reactions occur on the electrode surface, near the surface or in the bulk phase in two or quasi-two dimensions, and the relevant capacitance is generated [31,32]. In this pseudocapacitive charge storage behavior, the charge is stored on the surface of the material due to the faradaic reactions.…”
Section: Introductionmentioning
confidence: 99%
“…[28] Interestingly, with those advantages, Mg batteries can be regarded as a credible alternative for storage systems of the next generation. [29,30] The formation of dendrites when using liquid electrolytes presents a major safety issue in metal-anode batteries (Li or Na metal) because the thin metal needles can expand through the separator and induce a short circuit inside the battery, which can trigger exposure of harmful substances, flame, and explosions. [31][32][33] Nevertheless, Mg metal anode shows surprising dendrite-free behaviour during the stripping/plating process from low to medium current density or sometimes at high applied current density.…”
Section: Introductionmentioning
confidence: 99%
“…SHE, relatively higher than Li + /Li or Ca 2+ /Ca leading to a more favourable negative reduction potential [28] . Interestingly, with those advantages, Mg batteries can be regarded as a credible alternative for storage systems of the next generation [29,30] …”
Section: Introductionmentioning
confidence: 99%